PENGARUH FAKTOR EKONOMI MAHASISWA PROGRAM STUDI EKONOMI PEMBANGUNAN UNIVERSITAS MUHAMMADIYAH BERAU DAN HARGA TERHADAP PERMINTAAN BARANG DI TIKTOK SHOP - MEDYANA AYU KARTIKA (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2026)
Background: The rapid growth of e-commerce in Indonesia, driven by a large internet user base, has positioned TikTok Shop as a popular online shopping platform that integrates entertainment and interactive purchasing. University students, as digital natives, represent an active consumer segment on this platform, where economic factors such as income and purchasing power, along with price, are presumed to influence their demand for goods. Objective: This study aims to determine the effect of economic factors among Development Economics students at Universitas Muhammadiyah Berau and price on the demand for goods on TikTok Shop, both partially and simultaneously. Method: This study employs a quantitative method with primary data collected through questionnaires distributed to 88 respondents selected using purposive sampling, analyzed using multiple linear regression. Results: The results indicate that students' economic factors have a significant effect on demand for goods (tcount = 2.121 > ttable = 1.988; sig. 0.037 < 0.05). The price variable also has a significant effect on demand for goods (tcount = 2.784 > ttable = 1.986; sig. 0.007 < 0.05). Simultaneously, economic factors and price have a significant effect on demand for goods, with an Fcount value of 9.912 > Ftable 3.10 at a significance level of 0.000, explaining 18.9% of the variation in demand, while the remaining 81.1% is influenced by other factors outside the research model. Conclusion: It is concluded that economic factors and price are important determinants that business actors should consider to increase demand for goods on TikTok Shop, particularly among the student consumer segment.